Epistemology, curriculum and evaluation (A Relationship to be Rebuilt) (2010)
The limits of an instrumental and technical conception of the evaluation effects on the pedagogic rarefying are drawn, the evaluation is relocated in the field of pedagogy and it is shown articulated with some epistemological and curriculum visions that make sense, finally, it is presented some principles in order to think evaluation as an integrity.